Cassese's international criminal law. - Cassese, Antonio
Provides a clear account of the main substantive and procedural aspects of international criminal law. Adopting a combination of the classic common law and more theoretical approaches to the subject, it discusses: the historical evolution of international criminal law; the legal definition of the so-called core crimes (war crimes, crimes against humanity, genocide) plus aggression, torture and terrorism; the forms and modes of criminal responsibility; and the main issues related to the prosecution and punishment of international crimes at the national and international level, including amnesties, statutes of limitations, and immunities.